Moving towards personalized medicine - the broad use of aptamers for targeted theranostic - Sousa, André P. (2023)
Aptamers are short, single-stranded oligonucleotides synthesized in vitro from a randomized oligonucleotide library against a specific target. These molecules are capable of binding to a wide range of biological targets with high specificity and affinity. They present great advantages over antibodies with potential applications in research, diagnosis, and therapeutics. Specifically for tumors with late-stage identification and poor prognosis, like pancreatic cancer, the study of novel aptamers holds tremendous potential for cancer diagnosis and treatment. Along with cancer treatment, aptamers have also shown high potential in regulating the immune response and modulating several critical steps of signaling cascades, such as in immune checkpoints. In the context of microbiota and infection, aptamers are being studied to identify microbes and their metabolites. This assessment has the potential to improve the detection and management of infectious diseases while assisting us in better understanding health risks and treatment outcomes by tracking changes in the microbiota. In this review, the potential of aptamers is explored regarding their applications in cancer, immune, and microbiota therapy.